Knowledge, Attitude, and Practice of Libyan General Dentists and Specialists toward Cavity Disinfectants before Composite Restorations: A Cross-sectional Survey - Shamsah, Lubnah; Samia Alawjali (AlQalam Journal of Medical and Applied Sciences, 2025)
The innovative approach for dental caries management focuses on the maximum removal of bacteria from the carious lesion, while minimizing loss of tooth tissue. The use of cavity disinfectants effectively reduces the number of viable remaining bacteria. The present study aims to evaluate and compare the knowledge, attitude, and practice of different types of cavity disinfectants among Libyan general dentists and specialists. A cross-sectional online survey involving 151 dentists was carried out in Benghazi (Libya) using a validated 10-item questionnaire. Data were analyzed using chi-square tests, with significance set at p<0.05. Results showed that chlorhexidine (CHX) and sodium hypochlorite (NaOCl) are the most popular disinfectants, there was a statistically significant difference in regard of knowledge of participating groups toward (NaOCl), (EDTA) and hydrogen peroxide. The majority of the participants indicated the use of a cavity disinfectant before acid etching, and believed it can be applied for both shallow and deep cavities. The majority of the participants didn’t attend any lectures concerned of cavity disinfection; however, they expressed a positive attitude toward the effectiveness of them against bacteria. There was no significant difference between participating groups in regard of cavity disinfectant’s daily practice; the most commonly used disinfectants are CHX followed by NaOCl. The selection of a suitable disinfectant necessitates the understanding of disinfection mechanisms and their effects on the bond strength of the restorative material. النهج المبتكر للتحكم في تسوس الأسنان يركز على الإزالة القصوى للبكتيريا من التسوس، مع تقليل فقدان نسيج الأسنان إلى أدنى حد. إستخدام مطهرات التجاويف يقلل بشكل فعال من عدد البكتيريا الباقية. تهدف الدراسة الحالية إلى تقييم ومقارنة المعرفة والمواقف والممارسات حول أنواع مختلفة من مطهرات التجاويف بين أطباء الأسنان العامين والمتخصصين الليبيين. تم إجراء دراسة مقطعية عبر الإنترنت شملت 151 طبيب أسنان في بنغازي (ليبيا) باستخدام استبيان مكون من 10 أسئلة. تم تحليل البيانات باستخدام اختبارات مربع كاي مع تحديد الدلالة الإحصائية عند 0.05>P. أظهرت النتائج أن كلورهكسيدين و هيبوكلوريت الصوديوم هما المطهران الأكثر شيوعًا. وكان هناك فرق ذو دلالة إحصائية في معرفة المجموعات المشاركة حول هيبوكلوريت الصوديوم, ثنائي أمين الإيثيلين رباعي حمض الأسيتيك و بيروكسيد الهيدروجين. أشار أغلبية المشاركين إلى إستخدام مطهر التجاويف قبل الحفر الحمضي، وإعتقدوا أنه يمكن تطبيقه على التجاويف السطحية والعميقة. لم يحضر معظم المشاركين أي محاضرات بخصوص تطهير التجاويف، ومع ذلك، أبدوا موقفًا إيجابيًا إتجاه فعالية هذه المطهرات ضد البكتيريا. لم يكن هناك فرق ذو دلالة إحصائية بين المجموعات المشاركة حول الممارسة اليومية لإستخدام مطهرات التجاويف؛ كانت المطهرات الأكثر استخدامًا هي أن الكلورهكسيدين يليها هيبوكلوريت الصوديوم. إختيارالمطهر المناسب يتطلب فهم آليات التطهير وتأثيراتها على قوة ارتباط مادة الترميم